Antibiotics for acute respiratory infections in general practice: comparison of prescribing rates with guideline recommendations. Issue 2 (17th July 2017) - McCullough, Amanda R; Pollack, Allan J; Plejdrup Hansen, Malene; Glasziou, Paul P; Looke, David FM; Britt, Helena C; Del Mar, Christopher B
Abstract: Objective: To compare the current rate of antibiotic prescribing for acute respiratory infections (ARIs) in Australian general practice with the recommendations in the most widely consulted therapeutic guidelines in Australia ( Therapeutic Guidelines ). Design and setting: Comparison of general practice activity data for April 2010 – March 2015 (derived from Bettering the Evaluation and Care of Health [BEACH] study) with estimated rates of prescribing recommended by Therapeutic Guidelines . Main outcome measures: Antibiotic prescribing rates and estimated guideline‐recommended rates per 100 encounters and per full‐time equivalent (FTE) GP per year for eight ARIs; number of prescriptions nationally per year. Results: An estimated mean 5.97 million (95% CI, 5.69–6.24 million) ARI cases per year were managed in Australian general practice with at least one antibiotic, equivalent to an estimated 230 cases per FTE GP/year (95% CI, 219–240 cases/FTE/year). Antibiotics are not recommended by the guidelines for acute bronchitis/bronchiolitis (current prescribing rate, 85%) or influenza (11%); they are always recommended for community‐acquired pneumonia (current prescribing rate, 72%) and pertussis (71%); and they are recommended for 0.5–8% of cases of acute rhinosinusitis (current prescribing rate, 41%), 20–31% of cases of acute otitis media (89%), and 19–40% cases of acute pharyngitis or tonsillitis (94%). Had GPs adhered to the guidelines, they would have prescribed antibiotics for 0.65–1.36 million ARIs per year nationally, or at 11–23% of the current prescribing rate. Antibiotics were prescribed more frequently than recommended for acute rhinosinusitis, acute bronchitis/bronchiolitis, acute otitis media, and acute pharyngitis/tonsillitis. Conclusions: Antibiotics are prescribed for ARIs at rates 4–9 times as high as those recommended by Therapeutic Guidelines . Our data provide the basis for setting absolute targets for reducing antibiotic prescribing in Australian general practice.